ANALYSIS OF THE INFLUENCE OF KB FIELD OFFICERS' COMPETENCE AND WORK MOTIVATION IN SUPPORTING THE ACHIEVEMENT OF THE POST DELIVERY KB PROGRAM AT THE PPKB SERVICE OF LABUHANBATU UTARA DISTRICT IN 2023 - Rahayu, Sri; Ritonga, Ahmad Hafizullah; Br Bangun, Sri Melda (JURNAL KESMAS DAN GIZI (JKG), 2023)
The prevalence of postpartum family planning services in low and middle-income countries is 8% in the first month, 25% at 6 months, and 30% in the first 12 months. Even so, the state continues to be motivated to expand family planning services (family planning) through family planning commodities, training for family planning health workers, and integration of family planning services. However, currently, the number of family planning services has not been served properly. This study applies a quantitative approach, observational, and cross-sectional design. Through this approach, it is possible to measure the influence of the competence and work motivation variables at the PLKB in supporting the achievement of the Postpartum Family Planning program. The sample for this study were all PLKB/PKB officers at the North Labuhanbatu Regency PPKB Office with a total of 41 people who were determined using a total sampling technique and using a questionnaire instrument in measuring. A total of 41 respondents who were tested based on age, gender, education, length of work, and employment status showed that there was a significant influence between the competence of PLKB/PKB officers and the achievement of postpartum family planning programs, with a Pearson Chi-Square value of 11.896 and a p-value = 0.001 ( p<0.05). If viewed based on motivation, then between work motivation aspects of personal and altruistic goals, work motivation aspects of pride and self-satisfaction, work motivation aspects of self-recognition and support, and work motivation as a whole with the achievement of postpartum family planning programs with each value of Pearson Chi-Square of (11.896; 6.600; 4.490; 9.899) and each value of p = 0.001; 0.010; 0.034; 0.002 (p<0.05).